O trabalho do fogo: perfis de domicílios enquanto unidades de produção e reprodução nas Minas Gerais oitocentista - Mario Marcos Sampaio Rodarte (2008)
This work deals with the understanding of households organization and dynamics in Minas Gerais, Brazil, in the decade of 1830. In the pre-industrial societies the fogo, which is how the domestic unit is most commonly referred in the 19th century documents, differed of the modern household, by having aside its reproductive function other social and economic productive functions. Given the specificity of fogo as a multi-functional and hybrid domestic group it is important to take into consideration all these aspects when dealing with the understanding of the past societies. Instead of using the conventional form of household and family classification following Lasletts seminal work published in 1972, the framework used here is based on a different conception of household (das Ganze Haus) developed by Austrian researchers, like Mitterauer and Sieder (1982).Although the relationship to the head of the household is, certainly, an important characteristic it is far from fully explaining the complexity of household dynamics in the past alone.The database is formed by a large set of lists of inhabitants available for Minas Gerais in the 1830 decade. It is the largest database for that period known in Brazil, also. This peculiar (and happy) situation could be related to the role of Minas Gerais within the country as the most populous province. The database included around 85 thousand households, approximately 10% of Brazils, and these domestic unities represent satisfactorily the regional diversity of Minas Gerias. A typology of household was generated with 35 variables, by application of the method of Grade of Membership (GoM), based in fuzzy sets theory of Zadeh (1965).The most important result is to appoint a narrow relationship among the several forms of economical inserts of the households (especially, the one of the farmer, mining owner and merchant with slaves, and peasant, but also the one of the autonomous and salaried) and their multiple patterns of forms and sizes. It was also detected that mixed forms existed between two pure profiles, although less representative.